Perancangan Model Pengukuran Kinerja Lean dan Green Rantai Pasok Semen Secara Terintegrasi - Dina Rahmayanti; Utari Putri (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2011)
Abstract PT. Semen Padang is one of the reputable cement companies in Indonesia which is producing types of cement. Implementation of supply chain concept in PT. Semen Padang is very important to satisfy customers and stakeholders requirement. Performance measurement is a process to evaluate the supply chain effectiveness and efficiency in lean and green aspect. The problem is how to design performance measurement model which is integrating lean and green supply chain concepts. The objective of research is integrating lean and green supply chain concepts to design supply chain performance measurement of bag cement type. Integration of lean and green concept is designed by Balanced Scorecard (BSC) perspectives that consist of financial, customer, internal process business and learning and growth. Key performance indicators (KPI) are formulated and classified based on BSC perspectives. Next stage is pair wise comparison process to the weight value. Evaluation of KPI pair wise comparison based is conducted on expert opinion which is selected by consideration of their relevance knowledge and experience. The process of pair wise comparison is calculated to determine priority of the KPIs based on weight value by using Analytical Hierarchy Process (AHP) method. The weight of KPI will be arrange by descending to determine the priority. Model of performance measurement is validated by face validity method. Research result is obtaining 25 KPIs that derived from integration of lean and green supply chain concept of bag cement type. Grouping is consisting of 3 KPIs of financial, 4 KPIs of customer, 11 KPI s of internal process business and 7 KPI s of learning & growth. Result is showing that customer is most prioritized element in supply chain of bag cement type. Implementation of proposing model is coordination of departments and employee in context of information accessibility.